Method of manufacturing dental cutting mill blank

JP2025041519APending Publication Date: 2025-03-26TOKUYAMA DENTAL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024101956
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-13
Filing Date
2024-06-25
Publication Date
2025-03-26

Smart Images

  • Figure 2025041519000001_ABST
    Figure 2025041519000001_ABST
Patent Text Reader

Abstract

To provide a method for efficiently manufacturing a mill blank having a to-be cut par made of a hybrid resin (HR), by which the gradation of a natural tooth can be faithfully reproduced regardless of a shape and a dental prosthesis capable of obtaining a natural three-dimensional effect after treatment can be manufactured.SOLUTION: A mill blank is manufactured that includes a to-be-cut part having a specific gradation structure in which 3 to 9 color units (CU), which are regions having the same appearance color and a predetermined thickness, are connected in a height direction without forming a lamination interface, by using a process in which two kinds of HR raw material compositions giving HRs of a color A and a color B having a viscosity of 20 to 150 (Pa s) measured by a rotary viscometer at 25°C and a color difference of 5 to 20 are filled in a mold while being appropriately mixed by using a two-liquid mixing dispenser with a position control mechanism and then cured.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a dental cutting mill blank and a dental hardenable composition suitable for use in said method. [Background technology]

[0002] Dental prostheses used in dental treatment are generally formed by casting metal materials such as gold, silver, titanium, palladium alloys, etc., or by processing nonmetallic materials such as ceramics and hybrid resins (hereinafter sometimes abbreviated as "HR"), or by forming a core part from a metal material and a surface part such as a facing part from a nonmetallic material. Note that hybrid resin means a composite material in which an inorganic filler (hereinafter also referred to as "inorganic filler") is densely dispersed in a resin matrix, and is usually obtained by polymerizing and curing a paste-like polymerizable and curable composition containing a polymerizable monomer, an inorganic filler, and a polymerization initiator by applying pressure, heating, etc.

[0003] Dental prostheses entirely made of non-metallic materials have the advantage of being aesthetically pleasing and free of metal allergies. In addition, the recent development of digital image technology and computer processing technology has made processing easier, and the demand for dental prostheses is rapidly increasing. For example, as disclosed in Patent Document 1, a CAD / CAM system is being used in which a dental prosthesis is formed by cutting a dental processing blank made of a non-metallic material using a CAD / CAM device based on a photographed image of the oral cavity. Here, the dental processing blank means a cut body (also called a mill blank) that can be attached to a cutting machine in a CAD / CAM system, and usually has a cut part and a holding part such as a holding pin for making it possible to attach it to the cutting machine. As the cut part, a (solid) block formed into a rectangular or cylindrical shape, or a (solid) disk formed into a plate or plate shape, etc. are generally known, and a cut part made of hybrid resin (HR) is also known. In the present invention, the term "HR-based dental cutting mill blank" or "HR-based mill blank" includes a form in which a cutting part made of HR is integrated with a holding part.

[0004] In recent years, in dental crown restoration treatment, the number of situations where dental prostheses are required to have aesthetics such as color tone and appearance equal to or close to natural tissues has been increasing. In order to ensure such aesthetics, HR-type mill blanks are produced from multilayered HR-type mill blanks in which multiple layers of different colors are integrated, rather than from HR-type mill blanks of a single color tone. For example, Patent Document 2 describes a method for producing a multilayered HR-type mill blank using a fluid paste as an HR raw material and multiple mold units. According to this method, a multilayered dental processing blank can be produced by filling each mold unit with a fluid paste (hardenable composition) of a different color tone and stacking them. Moreover, even when a paste with low fluidity that is difficult to pour into a mold is used, it is said that it is possible to produce a multilayered dental processing blank consisting of multiple colors and compositions by suppressing the occurrence of defects such as a disturbance in the interface between pastes and voids in the paste.

[0005] In addition, as a tooth imitation technology different from the above-mentioned layered structure, Patent Document 3 proposes an HR-based mill blank in which the color tone changes continuously from one end of the blank to the other end, and a manufacturing method thereof. That is, Patent Document 3 discloses a method of manufacturing a dental cutting mill blank (HR-based mill blank) having the above-mentioned gradation (color tone changes continuously) structure by using an extruder such as a dispenser to fill a mixture of two types of fluid pastes (hardenable compositions) with different colors (HR raw materials) from one corner to the opposite corner in a mold (for example, from the lower corner to the upper opposite corner), continuously changing the mixing ratio of both pastes in the mixture, and hardening the filled paste. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2016-535610 [Patent Document 2] JP 2020-151339 A [Patent Document 3] US Patent Application Publication No. 2019 / 0247168 [Patent Document 4] Patent No. 6285909 [Patent Document 5] Patent No. 6349480 Summary of the Invention [Problem to be solved by the invention]

[0007] According to the manufacturing method of the HR-type mill blank disclosed in Patent Document 3 (hereinafter, also referred to as "the manufacturing method of Patent Document 3"), it is possible to solve the problem that the joint surface of the layers becomes discontinuous when a layered structure is formed. However, when the HR-type mill blank is manufactured by filling the paste while continuously changing the mixing ratio at a constant rate, the color tone differs slightly depending on the location even in a cross section having the same height, so that the color tone may be slightly deviated from the intended color tone depending on the position where cutting is performed. In addition, when a full-coverage crown is manufactured using the HR-type mill blank manufactured as described above, the color transition from the cervical part to the incisal part tends to have an appearance lacking in three-dimensionality when compared with an untreated natural tooth next to it. Furthermore, when multiple prostheses are manufactured to treat different parts at the same time, depending on the size of the treatment part, only a part of the cut part may be used, for example, a partial-coverage crown with a short crown length may be manufactured, but in this case, it has been found that an unnatural gradation may be displayed in the tooth after restoration.

[0008] Therefore, the present invention aims to provide a method for efficiently manufacturing dental cutting mill blanks that can be used to create dental prostheses that more faithfully reproduce the gradation of natural teeth without causing such problems and that provide a natural three-dimensional effect after treatment. [Means for solving the problem]

[0009] The present invention solves the above problems, and a first embodiment of the present invention is a method for manufacturing a mill blank for dental cutting, comprising: a hybrid resin having a columnar shape with a bottom surface and a top surface having substantially the same shape; and a cutting portion having a gradation structure in which the external color changes stepwise in the height direction when the direction from the bottom surface of the columnar body to the top surface, which is the tip, is defined as the height direction; The gradation structure is such that the regions exhibiting the same appearance color constitute "color units" of a predetermined thickness obtained by dividing the columnar body in the height direction by a plane horizontal to the bottom surface, and 3 to 9 "color units" having different appearance colors are continuously arranged in the height direction, The 3 to 9 "color units" are represented as "color unit n" by assigning unit numbers: n (where m is a natural number in the range of 3 to 9 representing the number of units) from 1 to m in order from the distal end to the proximal end, and the color of "color unit 1" located at the distal end is designated as "tip region color: A" and the color of "color unit m" located at the proximal end is designated as "proximal region color: B". Color difference between the distal end region color: A and the proximal end region color: B: ΔE AB is 5 to 20, In the "color unit 2" to "color unit m-1", the colors of these units are all intermediate colors C between the distal region color A and the proximal region color B, and change stepwise from an intermediate color close to the distal region color A to an intermediate color close to the proximal region color B from "color unit 2" to "color unit m-1". In addition, the color difference between the colors of adjacent units is ΔE C is 1 to 7, The manufacturing method includes: The method includes a raw material preparation step of preparing a paste-like HR raw material composition containing 100 parts by mass of a polymerizable monomer, 300 to 900 parts by mass of inorganic powder and granules constituted by inorganic particles, a polymerization initiator, and a colorant, the paste having a viscosity of 20 to 150 (Pa s) as measured with a rotational viscometer at 25°C; a filling step of filling the HR raw material composition into a mold corresponding to the shape of the cut part; and a hardening step of hardening the HR raw material composition filled in the mold, In the raw material preparation step, as the HR raw material compositions, a raw material composition A for "color unit 1" that gives the HR of the tip region color: A, a raw material composition B for "color unit m" that gives the HR of the base region color: B, and (m-2) types of HR raw material compositions for intermediate regions that have compositions equivalent to a mixture of the raw material composition A and the raw material composition B and give the appearance colors of the "color unit 2" to "color unit m-1" are prepared, The filling step includes: a tip region filling step of filling a necessary amount of the raw material composition A into the mold to form the "color unit 1"; A base end region filling step of filling a necessary amount of the raw material composition B into the mold to form the "color unit m"; and a filling step for filling a necessary amount of the HR raw material composition for the intermediate region into the mold to form the "color unit 2" to "color unit m-1", The filling step is (1) Pattern 1, in which the distal region filling step, the intermediate region filling step, and the proximal region filling step are performed in this order, or (2) Pattern 2 in which the base region filling step, the intermediate region filling step, and the tip region filling step are performed in this order. This is done in one of the following patterns: In the filling step, the filling is performed using storage tanks capable of separately holding two types of fluids and a discharge device capable of uniformly mixing the two types of fluids held in each storage tank at an arbitrary ratio and discharging the mixture from a discharge port, In the pattern 1, the discharge device is used to discharge only the raw material composition A to perform the tip region filling step, and then, when mixing the raw material composition A and the raw material composition B in the intermediate region filling step, the ratio of the raw material composition A in the resulting mixture is gradually reduced to prepare an HR raw material composition for the intermediate region for each "color unit", which is discharged sequentially to perform the intermediate region filling step, and then, only the raw material composition B is discharged to perform the base region filling step, In the pattern 2, the base end region filling step is performed by discharging only the raw material composition B using the discharge device, and then, in the intermediate region filling step, when mixing the raw material composition A and the raw material composition B, the ratio of the raw material composition B in the resulting mixture is gradually reduced to prepare an intermediate region HR raw material composition for each "color unit", which is sequentially discharged to perform the intermediate region filling step, and then, the tip region filling step is performed by discharging only the raw material composition A. This is a method for producing a mill blank for dental cutting, characterized in that

[0010] In the manufacturing method of the above embodiment (hereinafter also referred to as the "manufacturing method of the present invention"), in the intermediate region filling step, the raw material composition A and the raw material composition B are mixed at different mixing ratios to prepare the (m-2) types of intermediate region HR raw material compositions that give the colors of the "color unit 2" to "color unit m-1", and in the pattern 1, the intermediate region HR raw material compositions from the raw material composition for "color unit 2" to the raw material composition for "color unit m-1" are prepared in sequence and the amount required to form each "color unit" is filled into the mold, and in the pattern 2, the intermediate region HR raw material compositions from the raw material composition for "color unit m-1" to the raw material composition for "color unit 2" are prepared in sequence and the raw material composition is changed to fill the mold in the amount required to form each "color unit".

[0011] In the above preferred embodiment, the position within the mold is expressed in a coordinate system in which an arbitrary point on the bottom surface of the mold is the origin, the horizontal and vertical directions of the bottom surface are the x-axis and y-axis, respectively, and the height direction is the z-axis. (m-1) z coordinates corresponding to the heights of the boundaries between m "color units" to be formed within the mold are expressed as z1 to z2 from the bottom surface side. m-1 When In the filling step, the raw material compositions for the various "color units" are filled into the mold using the discharge device that can freely control the position of the discharge port in the front-back direction, the left-right direction, and the height direction. (i) locating the position of the ejection port at the start of filling at the origin; (ii) discharging the HR raw material composition from the discharge port at a predetermined flow rate while moving the position of the discharge port in the x-axis direction and / or the y-axis direction to scan the entire area on the bottom surface once, thereby forming a filling area at the bottom of the mold having a uniform thickness corresponding to the single scan; (iii) after the scanning of (ii) is completed, moving the position of the discharge port in the z-axis direction to a height equal to or higher than the upper surface of the lowermost filling area of ​​the mold; (iv) while discharging the HR raw material composition at a predetermined flow rate in the same manner as in (ii) above, the position of the discharge port is moved in the x-axis direction and / or the y-axis direction to scan the entire area on the upper surface of the bottommost filling area of ​​the mold once, thereby forming a grown filling area with an additional uniform thickness corresponding to the one scan; (v) continuously repeating the operations (iii) and (iv) using the grown filling area as a base; This is done by The ratio of the raw material composition to be discharged is changed so that the thickness of the formed growth filling region is within the range of z1 to z m-1 It is preferable to carry out the operations (ii) to (iv) above so that the raw material composition of the next "color unit" is discharged from the discharge outlet at a timing that coincides or substantially coincides with each height of the first and second "color units".

[0012] The second aspect of the present invention is a dental hardenable composition for an HR raw material composition in the method for producing a mill blank for dental cutting of the present invention, Polymerizable monomer: 100 parts by mass, inorganic powder / granules composed of inorganic particles: 300 to 900 parts by mass, a polymerization initiator and a colorant are included, In a polyfunctional radically polymerizable monomer compound having 2 to 6 radically polymerizable groups represented by CH2=C(R)-COO- or CH2=C(R)-CONH- (wherein R in these groups is a hydrogen atom or a methyl group) in the molecule, when the number of atoms constituting the main chain of the divalent organic group having the largest number of atoms constituting the main chain (the longest series of covalently bonded atoms) among the divalent organic groups interposed between any two radically polymerizable groups selected from the 2 to 6 radically polymerizable groups contained in the molecule of the polyfunctional radically polymerizable monomer compound is α, the polyfunctional radically polymerizable monomer compound having α of 1 to 9 is defined as a short-chain monomer, and the polyfunctional radically polymerizable monomer compound having α of 10 to 60 is defined as a long-chain monomer, the polymerizable monomer comprises the short-chain monomer and the long-chain monomer, and the content of the short-chain monomer in the polymerizable monomer is 45 to 90 mass %. The dental hardenable composition is characterized in that

[0013] In the dental hardenable composition of the above form (hereinafter also referred to as "dental hardenable composition of the present invention"), it is preferable that the short-chain monomer is composed of at least one compound selected from the group consisting of alkyl dimethacrylates and polyalkylene glycol dimethacrylates, and the long-chain monomer is composed of at least one compound selected from urethane (meth)acrylates.

[0014] It is also preferable that the inorganic powder or granules are composed of spherical or nearly spherical inorganic particles, contain inorganic spherical powder or granules having a particle diameter D50p of 50 to 500 nm, which is the cumulative 50% particle diameter from the small diameter side in a number-based particle size distribution measured by a laser diffraction method, and that the amount of the inorganic nearly spherical powder or granules in the inorganic powder or granules is 40 mass% or more.

[0015] Furthermore, the dental curable composition preferably has a viscosity of 20 to 150 (Pa·s) at 25° C. as measured with a rotational viscometer. Effect of the Invention

[0016] According to the manufacturing method of the present invention, regardless of the shape of the dental prosthesis to be manufactured (for example, in the case of manufacturing a crown, regardless of whether it is a full-covered crown or a partial-covered crown with a short crown length), it is possible to efficiently manufacture a mill blank suitable for manufacturing a dental prosthesis that reproduces the gradation of a natural tooth more faithfully and provides a natural three-dimensional effect after treatment. Moreover, since it is not a laminate having a clear lamination interface but has a single-layer structure in which the appearance color changes stepwise in the height direction, there is no disturbance of the gradation due to the disturbance of the lamination interface, and further there is no trouble such as breakage along the lamination interface during cutting. Furthermore, due to the use of an HR raw material composition with a high content of inorganic powder and particles (inorganic filler), it is possible to manufacture a mill blank that can manufacture a high-strength dental prosthesis. In this case, even if a discharge device having a discharge port with a small opening area (opening diameter) is used, the HR raw material composition used can be filled into a mold without any problems, even if a discharge device having a discharge port with a small opening area (opening diameter) is used. [Brief description of the drawings]

[0017] [Figure 1] This figure is a schematic diagram showing a cross section of a cut portion of a typical mill blank obtained by the manufacturing method of the present invention, in which the vertical direction represents the height direction (z-axis direction). [Diagram 2] This figure is a schematic diagram for explaining the configuration of a discharge device that can be suitably used in the manufacturing method of the present invention. [Diagram 3] This figure is a schematic diagram showing the state (changes) on the bottom surface when forming the bottommost filling region of the mold when performing the filling step in the manufacturing method of the present invention using the discharge device shown in Figure 2. The arrows in the figure indicate the movement direction of the nozzle discharge port. [Figure 4]This figure is a schematic diagram showing the state (changes) of the mold as viewed from the main side direction when the filling region at the bottom of the mold is formed (left figure) and when the growing filling region is formed above it (right figure) during the filling step in the manufacturing method of the present invention using the discharge device shown in Figure 2. The arrows in the figure indicate the movement direction of the nozzle discharge port. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] According to the manufacturing method of Patent Document 3, it is possible to give a continuous shade gradient to the cut part made of HR, but when the paste filling is performed while continuously changing the mixing ratio of two types of paste at a constant rate as described above, it is difficult to obtain a blank from which a dental prosthesis with a color tone and three-dimensional effect that harmonizes with natural teeth can be fabricated. This is thought to be due to the fact that the color tone of natural teeth is visually recognized as the result of the fusion of the colors of the dentin and the enamel that covers it, reflecting their internal structure, and not only are the original colors of the dentin and enamel significantly different, but the thickness ratio of the two does not necessarily change continuously and uniformly from the cervical side to the incisal side.

[0019] In contrast, according to the manufacturing method of the present invention, in order to reproduce the discontinuous color change of a natural tooth from the cervical area to the incisal end, the gradation of the cut area is not a continuous change in color, but rather changes discontinuously (in steps) in the height direction, and the thickness of the "color unit" which is the area exhibiting each color is made thick at both ends and thin in the central area, and furthermore, in the central area, the color changes in the height direction are finely stepped, creating optical illusion effects such as the Chevreul illusion and Mach bands (where the interface between one uniform layer and another layer appears to be emphasized), which are partially emphasized and perceived by humans, making it possible to efficiently manufacture mill blanks which can reproduce the discontinuous appearance seen in natural teeth.

[0020] The manufacturing method of the present invention is based on the knowledge that the above-mentioned mill blanks can be efficiently manufactured by filling the inside of a mold with an HR raw material composition using a discharge device that can uniformly mix the two types of fluids held in each tank at any ratio and discharge the mixture from the discharge port, such as a volumetric two-liquid mixing dispenser. However, when such a filling method is adopted, it has become clear that it is difficult to fill an HR raw material composition with a high content of inorganic powder and particles (inorganic filler) when the mold size is small or the number of "color units" is large, and the opening diameter of the discharge port of the discharge device must be small, for example, about 2 mm. As a result of further investigations to solve such a new problem, it has been found that, depending on the composition of the polymerizable monomer, the viscosity can be kept relatively low and the dischargeability is not easily reduced even if the content of inorganic powder and particles (inorganic filler) is increased, and this has led to the completion of the present invention.

[0021] The mill blank obtained by the production method of the present invention and the production method of the present invention will be described in detail below.

[0022] 1. Mill blank obtained by the manufacturing method of the present invention The mill blank obtained by the manufacturing method of the present invention is a mill blank for dental cutting, which includes a cutting portion made of a hybrid resin having a columnar shape with a bottom surface and a top surface having substantially the same shape, and is characterized in that the cutting portion has a specific gradation structure.

[0023] 1-1. Material and shape of the part to be cut The mill blank obtained by the manufacturing method of the present invention has a cut part made of hybrid resin (HR), and the shape of the cut part is a columnar shape with the bottom surface and the top surface being substantially the same shape. Mill blanks having a cut part of such material and shape are common to HR-based mill blanks, and the basic material and shape of the mill blank obtained by the manufacturing method of the present invention are not particularly different from common HR-based mill blanks.

[0024] For example, regarding the shape, a columnar or disk-shaped body that can be set in a commercially available dental CAD / CAM system and that is of a size that can process one or more teeth can be used without any particular restrictions. Examples of suitable sizes include a 40 mm x 20 mm x 15 mm prism suitable for making a single-tooth missing bridge; a 15 mm x 8 mm x 8 mm or 15 mm x 10 mm x 10 mm prism suitable for making an inlay or onlay; a 20 mm x 18 mm x 14 mm, 15 mm x 12 mm x 10 mm, 15 mm x 12 mm x 6.5 mm, 18 mm x 14 mm x 12 mm, 18 mm x 14 mm x 16 mm, 15 mm x 14.5 mm x 14.5 mm, 18 mm x 14.5 mm x 14.5 mm, or 18 mm x 14.5 mm x 16 mm prism suitable for making a full crown; and a disk shape with a diameter of 90 to 100 mm and a thickness of 10 to 28 mm suitable for making a long-span bridge or denture base.

[0025] Considering the manufacturing method of the present invention, a blank with a large volume such as a disk requires a long time to fill with the HR raw material composition during manufacturing compared to a smaller blank, and the layer is difficult to achieve smoothness, so a cylindrical or prismatic shape is preferable. On the other hand, it is difficult to feel the color difference in a small processed product. Therefore, it leads to more effective and low-cost manufacturing in blanks with a certain thickness and size. By setting the height of the cut part to 6 to 25 mm, it is possible to accommodate teeth of general size. If the height is small, it is difficult to obtain the effect of color change described later, so 8 mm or more is preferable, and 10 mm or more is most preferable. If the height is large, it is easy to accommodate various tooth crown shapes and it is easy to clearly express the color difference with the middle, but if it is more than 25 mm, the number of parts to be cut in vain increases.

[0026] The raw materials for HR will be described in detail in the explanation of the production method of the present invention (dental curable composition of the present invention).

[0027] 1-2. Gradient structure The cut portion of the mill blank of the present invention has a gradation structure in which the appearance color changes stepwise in the height direction, when the direction from the bottom surface of the columnar body to the top surface at the tip is defined as the height direction. In order to obtain the effects described above, the gradation structure must satisfy all of the conditions (1) to (3) below (hereinafter, a gradation structure that satisfies these conditions will also be referred to as the "gradation structure of the present invention").

[0028] (1) The region exhibiting the same appearance color constitutes a "color unit" of a predetermined thickness obtained by dividing the columnar body in the height direction by a plane horizontal to the bottom surface, and 3 to 9 "color units" having different appearance colors are arranged continuously in the height direction. However, the "plane horizontal to the bottom surface" does not necessarily have to be a flat surface, and may be a curved surface (such as a wavy surface) with minute unevenness {with a height difference of, for example, 1.0 mm or less, preferably 0.5 mm or less} that is unavoidably or intentionally formed with the "plane horizontal to the bottom surface" as the reference surface.

[0029] (2) The 3 to 9 "color units" are represented as "color unit n" by assigning unit numbers: n (where n is a natural number from 1 to m) from 1 to m (where m is a natural number from 1 to m) in such a way that the numerical value increases from the distal end to the proximal end, and the color of the "color unit 1" located at the distal end is designated as "distal region color: A" and the color of the "color unit m" located at the proximal end is designated as "proximal region color: B." The color difference between the distal region color: A and the proximal region color: B is: ΔE AB is between 5 and 20.

[0030] (3) In the "color unit 2" to "color unit m-1", the colors of these units are all intermediate colors C between the distal region color A and the proximal region color B, and change gradually from an intermediate color close to the distal region color A to an intermediate color close to the proximal region color B from "color unit 2" to "color unit m-1". In addition, the color difference between the colors of adjacent units is ΔE C is 1 to 7.

[0031] The gradation structure of the present invention will be described below with reference to FIG. 1, which is a schematic longitudinal cross-sectional view (cut along a plane perpendicular to the bottom surface 2) of a cut part 1 made of a columnar body having six "color units" (m=6). The gradation structure 10 of the present invention shown in FIG. 1 includes a bottom surface 2 and a "color unit 6" 14 that exhibits a "base end region color: B", a "color unit 1" 19 that includes an upper surface and exhibits a "tip end region color: A", and four "color units 2" 18 to "color units 5" 15 that are interposed between the bottom surface 2 and exhibit an intermediate color: C between the colors A and B. However, the gradation structure of the present invention is not limited to that shown in FIG. 1, and for example, m, which represents the number of "color units", may be 3 to 9, and is preferably 3 to 7.

[0032] As described in (1) above, the "color unit" refers to an area of ​​a given thickness obtained by dividing the columnar body in the height direction by a plane horizontal to the bottom surface, and exhibiting the same appearance color, but the boundary surface between adjacent "color units" due to the manufacturing method does not need to be a precise plane, and may be any surface that can be regarded as substantially flat. For example, the boundary surface may be a curved surface (e.g., a wavy curved surface) with minute irregularities {with a height difference of, for example, 1.0 mm or less, preferably 0.5 mm or less}, with the "plane horizontal to the bottom surface" as the reference surface.

[0033] In addition, a "color unit" is a region that exhibits the same appearance color, and the appearance color in any partial region within a single "color unit" is the same. Here, "same" means that the appearance color is not intentionally changed, and it is acceptable that the appearance color of both "color units" is a mixed color of the appearance colors of the two "color units" in a very thin region at the boundary between adjacent "color units", or that the appearance color varies slightly due to inevitable variations in the composition when mixing two types of curable compositions that are raw materials for HR to prepare a filling curable composition. For example, as in the method disclosed in Patent Document 3, when the curable composition that is the raw material for HR is continuously extruded into a mold while changing its composition slightly "continuously", filling it, and then cured, the appearance color also changes according to the change in composition, so it is not possible to form a "color unit".

[0034] The cut portion of the mill blank of the present invention may have a laminate structure in which each "color unit" forms an (independent) single layer and these are stacked (with a clear lamination interface between the layers), but it is preferable that each "color unit" is a highly integrated single-layer structure because it does not have a lamination interface that may contain disorder or defects and may cause peeling, etc. Such a single-layer structure can be obtained in the manufacturing method of the present invention, as described below, by scanning a nozzle to continuously extrude and fill the curable composition, which is the raw material of the HR that constitutes each "color unit," into a mold while slightly changing its composition "step by step" using a filling device such as a two-liquid mixing dispenser.

[0035] The thickness (height) of the "color unit 1" (19 in FIG. 1) located at the most distal end of the columnar body constituting the cut portion of the mill blank of the present invention and the "color unit 6 (=m)" (14 in FIG. 1) located at the most proximal end is preferably 15 to 35% of the total thickness (height) of the columnar body, and more preferably 20 to 30%. In this case, the thickness (height) of the "unit 1" and the thickness (height) of the "unit m" may be different. If the "color unit 1" and the "color unit m" are thinned beyond the lower limit, it becomes difficult to clearly reproduce the incisal edge and cervical part of the tooth, and it tends to be difficult to deal with workpieces of different shapes. On the other hand, if they are too thick beyond the upper limit, the incisal edge and cervical part of the tooth can be clearly reproduced, but the color tone change between the "color unit 2" (18 in FIG. 1) to the "color unit 5 (=m-1)" (15 in FIG. 1) tends to be abrupt and unnatural.

[0036] Color difference between "tip region color: A" and "base region color: B": ΔE AB must be 5 to 20. This is based on the requirement that one (color A or color B) is usually a shade that corresponds to the shade of the apical region (incisal side) of the tooth, and the other (B or A) is a shade that corresponds to the shade of the cervical side of the tooth (specifically, the cervical region and its adjacent region). ΔE ABIf it is outside the above range, the combination of the color tone of the tip region and the color tone of the cervical region and its neighboring regions of a single natural tooth will be unnatural.

[0037] The color difference (ΔE) is an index that indicates the degree of difference between two colors, and the larger the value, the more different the color tones of the two are. * ) is a method for comparing two contrasting tones by measuring the lightness of the two tones. * , and again indicate the hue and chromaticity * , and b * Expressed as L * a * b * The numerical values ​​of each coordinate axis in the color space (color system) (L * Value, a * value and b * Difference (ΔL * , Δa * and Δb * ) means ΔE determined by the following formula: ΔE={(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2 In addition, the above-mentioned L * Value, a * value and b * The value is the L value obtained by measuring the spectral reflectance of a sample with a thickness of 1.0 ± 0.1 mm using a spectrophotometer (for example, Tokyo Denshoku's "TC-1800MKII") against a white background. * , a * and b *It is determined by. Specifically, in the case of a color difference meter, "TC-1800MKII" manufactured by Tokyo Denshoku, the measurement conditions are: halogen lamp: 12V100W, measurement wavelength range 380-780nm, reflected light 0°d method (JIS Z8722), measurement area 5mmφ, background color white (a standard white plate is placed on the cured body to block light). The preparation and measurement of the measurement sample can be performed by (i) cutting out the center of each color unit from the cut part in a direction parallel to the bottom surface (exposing the cross section of a single color unit) to prepare a measurement test piece and measuring it with a color difference meter, (ii) cutting out the center of each color unit from the cut part in a direction parallel to the bottom surface (exposing the vertical cross sections of all color units) to prepare a measurement test piece and measuring it by scanning it in a line from the tip to the base end, or (iii) when the composition of the raw material composition of the HR constituting each "color unit" is clear, a sample prepared using the raw material composition of the same composition can be measured with a color difference meter. When using the above method (i), measurements are taken on both sides of the sample, and the average value is used as the L value for the "color unit." * a * b * In addition, when the above method (ii) is adopted, the measured value near the center of each color unit is used as the L value of the "color unit". * a * b * value.

[0038] It is optional to determine whether the tip region color: A or the base region color: B corresponds to the color tone of the tip region (incisal side) of a natural tooth, but in the embodiment shown in FIG. 1, it is color A. When the tip region color: A corresponds to the color tone of the tip region (incisal side) of a natural tooth, the color A is usually selected from A1, A2, and A3 in the shades of Vita's 16-color shade guide, and the base region color: B, which corresponds to the color tone of the cervical side of a natural tooth, is usually selected from A3, A3.5, and A4. It is also possible to increase the color variation that can be created from the combination of the tip region color: A and the base region color: B by making the tip region color: A a lighter shade than A1 and the base region color: B a darker shade than A4.

[0039] In the gradation structure 10 of the present invention, the colors of the "color unit 2" 18 to the "color unit 5 (=m-1)" 15 are all intermediate colors C between the distal end region color A and the proximal end region color B, and change stepwise from an intermediate color close to color A to an intermediate color close to color B from the "color unit 2" to the "color unit m-1". In addition, the color difference between the colors of the adjacent units is ΔE C The number of colors must be between 1 and 5. In other words, the intermediate color between color A and color B belongs to C, and multiple colors that are different from each other are classified as C. n (where n is a natural number from 2 to m-1, and the smaller the value of n, the closer the intermediate color is to color A, and the larger the value of n, the closer the intermediate color is to color B.) m-1 and the intermediate color C n-1 and the intermediate color C n Color difference: ΔE C must always be 1 to 7, and more preferably 1 to 5. In addition, the color difference between color A and color C2: ΔE AC2 And color B and color C m-1 Color difference: ΔE BCm-1 It is preferable that each ΔE C , ΔE AC2 and ΔE BCm-1 The individual values ​​may be different from each other as long as they are within the above range. For example, the range of change may be gradually increased or decreased from "color unit 1" to "color unit m", or the central part may be set larger.

[0040] 2. The manufacturing method of the present invention The manufacturing method of the present invention is a method for manufacturing the mill blank of the present invention, and similar to the general manufacturing method of conventional HR-based mill blanks, a paste-like HR raw material composition containing a polymerizable monomer, an inorganic filler, a polymerization initiator and a colorant is prepared (raw material preparation step), which is then filled into a mold (filling step) and hardened (hardening step) to obtain a cuttable part, but is characterized in that in the raw material preparation step, two types of specific HR raw material compositions are prepared, and in the filling step, a special filling method using these compositions is adopted, which makes it possible to efficiently manufacture the mill blank of the present invention. Below, each step in the manufacturing method of the present invention will be described, including the points that are different from the conventional general method.

[0041] 2-1. Raw material preparation process In the raw material preparation step, a paste-like HR raw material composition (which is also the dental curable composition of the present invention) containing 100 parts by mass of a polymerizable monomer, 300 to 900 parts by mass of inorganic powder and granules composed of inorganic particles, a polymerization initiator, and a colorant and having a viscosity (measured with a rotational viscometer) of 20 to 150 (Pa·s) at 25°C is prepared. As the HR raw material composition, raw material composition A for "color unit 1" that gives the HR of the tip region color: A and raw material composition B for "color unit m" that gives the HR of the base region color: B are prepared, and further, as the HR raw material composition for forming the "color unit 2" to "color unit m-1", HR raw material compositions for the intermediate region of (m-2) types that have a composition equivalent to a mixture of the raw material composition A and the raw material composition B and give the appearance color of each "color unit" are prepared. In this case, the (m-2) type HR raw material composition for the intermediate region is prepared by directly mixing the raw material composition A for the “color unit 1” and the raw material composition B for the “color unit m” at different mixing ratios.

[0042] 2-1-1. Polymerizable monomers The polymerizable monomer that is the raw material of the paste-like HR raw material composition is one whose hardened form becomes the resin matrix of HR. As the polymerizable monomer, any radically polymerizable monomer that makes the HR raw material composition have the above-mentioned viscosity can be used without any particular limitation. In order to obtain a dental polymerizable hardenable composition, a polymerizable monomer having a radically polymerizable group represented by CH2=C(R)-COO- or CH2=C(R)-CONH- (wherein R in these groups is a hydrogen atom or a methyl group) can be suitably used, and it is particularly preferable to use a polyfunctional radically polymerizable monomer compound having 2 to 6 of these radically polymerizable groups in the molecule.

[0043] From the viewpoint of reliably obtaining a product having a viscosity in the above-mentioned range while containing the inorganic powder and granules in the above-mentioned content, it is preferable that, among the divalent organic groups interposed between any two radically polymerizable groups selected from the radically polymerizable groups contained in the molecule of the polyfunctional radically polymerizable monomer compound, the number of atoms constituting the divalent organic main chain having the largest number of atoms constituting the main chain (the longest series of covalently bonded atoms) is α, the polyfunctional radically polymerizable monomer compound having α of 1 to 9 is a short-chain monomer, and the polyfunctional radically polymerizable monomer compound having α of 10 to 60 is a long-chain monomer, the polymerizable monomer is composed of the short-chain monomer and the long-chain monomer, and the content of the short-chain monomer contained in the polymerizable monomer is 45 to 90 mass% (more preferably 50 to 85 mass%).

[0044] In addition, when various polyfunctional radical polymerizable monomers to be short chain length monomers and long chain length monomers have a molecular weight distribution (consisting of a mixture of multiple compounds with different α), the value of α is adopted as the value of the compound with the highest content (molar fraction). In addition, when the polyfunctional radical polymerizable monomer compound is a commercially available product whose molecular weight distribution is unknown, the composition can also be determined by an analysis method using gel permeation chromatography (GPC).

[0045] The short chain monomer preferably comprises at least one compound selected from the group consisting of alkyl dimethacrylates and polyalkylene glycol dimethacrylates.

[0046] Here, the divalent organic group interposed between any two radically polymerizable groups in the alkyl dimethacrylate may be linear or branched.

[0047] The polyalkylene glycol is a compound in which a radical polymerizable group is bonded to an alkylene glycol or a group in which multiple alkylene glycols are linked together, and specifically includes ethylene glycol, trimethylene glycol, propylene glycol, tetramethylene glycol, or a compound in which multiple compounds are linked together (e.g., tri(ethylene glycol)). Among these, ethylene glycol or a compound in which multiple ethylene glycols are linked together is preferred, and diethylene glycol and triethylene glycol are more preferred.

[0048] Examples of short-chain monomers that can be suitably used include neopentyl glycol dimethacrylate (NPG) in which α is 3, diethylene glycol dimethacrylate (2G) in which α is 5, triethylene glycol dimethacrylate (3G) in which α is 8, and 1,6-hexanediol dimethacrylate (HD) in which α is 6.

[0049] On the other hand, the long chain monomer is preferably composed of at least one compound selected from urethane (meth)acrylates. Here, urethane (meth)acrylate means a compound having a urethane group in a divalent organic group interposed between any two radical polymerizable groups, and preferably contains two or more urethane groups. Examples of suitable long chain monomers include 1,6-bis(methacrylethyloxycarbonylamino)trimethylhexane, in which α is 16; α,ω-bis(pentaerythritol triacryloxycarbonylamino)hexane (UA306H), in which α is 18; and α,ω-bis(acrylethyloxycarbonylamino)decaTHF (UA4200), in which α is 59.

[0050] 2-1-2.Inorganic powder and granules The inorganic powder functions as a filler (inorganic filler) added to increase the strength of the HR cured body, increase the elastic modulus to reduce deflection, increase abrasion resistance, suppress polymerization shrinkage, and adjust fluidity. The content of the inorganic powder in the HR raw material composition may be 300 to 900 parts by mass per 100 parts by mass of the polymerizable monomer, but from the viewpoint of achieving both high strength of the mill blank and low viscosity of the dental curable composition, it is more preferable that the content is 350 to 700 parts by mass, and particularly preferable that the content is 350 to 500 parts by mass.

[0051] As the inorganic powder, inorganic powder used as an inorganic filler in dental hardenable compositions can be used without any particular restrictions. From the viewpoint of easy adjustment of viscosity to the above range and surface smoothness when used as a dental prosthesis, the inorganic powder is preferably composed of spherical or nearly spherical inorganic particles, and contains inorganic spherical powder having a particle diameter D50p (hereinafter also referred to as "average particle diameter" or "average particle diameter") of 50 to 500 nm, more preferably 100 to 400 nm, which is 50% by mass or more of the particle size distribution based on the number of particles, and the amount of the inorganic nearly spherical powder in the inorganic powder is preferably 40% by mass or more.

[0052] In addition, as the "inorganic spherical powder particles composed of spherical or nearly spherical inorganic particles" used as an inorganic filler for dental curable compositions, those obtained by the so-called sol-gel method are known, and the inorganic spherical powder particles obtained by this method have a very sharp particle size distribution, and when dispersed in a liquid dispersion medium, they are easily dispersed as primary particles by ultrasonic irradiation, etc., so that the D50p (average particle size) measured by the above method is in good agreement with the average primary particle size measured using a scanning electron microscope (SEM). Therefore, the above D50p can also be regarded as the average primary particle size.

[0053] Among the inorganic particles constituting the inorganic powder, silica-based composite oxide particles are particularly preferred because they have a large amount of silanol groups on the particle surface, making it easy to perform surface modification using a silane coupling agent or the like. Particles such as silica-zirconia, silica-titania, silica-titania-barium oxide, and silica-titania-zirconia are suitable because they have high X-ray contrast properties. Furthermore, silica-titania particles and silica-zirconia particles are the most preferred because they provide a cured product with better abrasion resistance. In addition, from the viewpoint of improving the flowability of the dental curable composition, the particles constituting the inorganic powder may be blended as an organic-inorganic composite powder composed of organic-inorganic composite particles (composed of a composite material of resin and inorganic powder). When the HR raw material composition contains an organic-inorganic composite powder, the content of the inorganic powder in the HR raw material composition includes the amount of the inorganic powder contained as the organic-inorganic composite powder. For example, when using w1 (parts by mass) of inorganic powder (not organic-inorganic composite) in combination with w2 (parts by mass) of organic-inorganic composite powder with an inorganic powder content of 80% by mass, the content of the inorganic powder in the HR raw material composition is w1 + 0.8 × w2 (parts by mass).

[0054] 2-1-3. Polymerization initiator The polymerization initiator is not particularly limited as long as it has the function of polymerizing and curing the polymerizable monomer. The polymerization method of the curable composition may be a reaction by light energy such as ultraviolet light or visible light (hereinafter referred to as photopolymerization), a chemical reaction between a peroxide and an accelerator, or a method by heat energy (hereinafter referred to as thermal polymerization), and any of these methods may be used. Photopolymerization and thermal polymerization are preferred because the timing of polymerization can be freely selected by external energy such as light or heat, and the operation is simple. Thermal polymerization is particularly preferred because it is difficult to cause polymerization unevenness due to light irradiation and the polymerization reaction can be performed uniformly. In addition to the reducing agent compound, a photoacid generator may be added to the photopolymerization initiator. These polymerization initiators may be used alone, or two or more of them may be mixed and used. It is also possible to combine multiple initiators with different polymerization methods. The amount of the polymerization initiator may be selected according to the purpose, and is usually 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the polymerizable monomer.

[0055] The coloring agent is blended to control the color tone of the paste and, by extension, the color tone of the hybrid resin, which is the hardened product of the paste. As the coloring agent, any coloring substance such as a pigment or dye that has been conventionally used for dental purposes can be used without any particular limitation, and these may be blended alone or in appropriate combination in the required amount according to the desired color (A or B).

[0056] 2-1-4. Viscosity of HR raw material composition The viscosity of the HR raw material composition at 25°C is preferably 20 to 150 (Pa·s). Here, the viscosity is measured by a rotational method, specifically, by a CS rheometer (Anton Paar MCR302) using a parallel plate of φ20 mm at 25°C and a shear rate of 2 (1 / s). If the viscosity is lower than 20 (Pa·s), the paste interface is disturbed when the paste is filled into the mold in layers, and the color transition tends to be unnatural, and if the viscosity is higher than 150 (Pa·s), it tends to be difficult to discharge with a dispenser. This viscosity is more preferably 30 to 60 (Pa·s).

[0057] 2-1-4. How to mix each component Regarding the kneading method when preparing raw material composition A and raw material composition B or compositions that are raw materials for these by mixing predetermined amounts of the above components, it is preferable to knead using a kneading device such as a planetary motion mixer, because it is possible to satisfy the above dispersion conditions in a short time and scale-up production is easy. In terms of enabling continuous kneading, it is also possible to use a single-screw extrusion kneader or a multi-screw kneader. In addition, it is preferable to adopt a method of degassing under reduced pressure, because it is possible to remove air bubbles in a short time.

[0058] 2-2. Filling process The filling process includes a tip region filling process in which a necessary amount of the raw material composition A is filled into the mold to form the "color unit 1", a base region filling process in which a necessary amount of the raw material composition B is filled into the mold to form the "color unit m", and a middle region filling process in which a necessary amount of the (m-2) type of HR raw material composition for the middle region is filled into the mold to form the "color unit 2" to "color unit m-1".

[0059] These steps are performed in either pattern (1) a pattern 1 in which the filling step for the tip region, the filling step for the intermediate region, and the filling step for the base region are performed in that order, or (2) a pattern 2 in which the filling step for the base region, the filling step for the intermediate region, and the filling step for the tip region are performed in that order.

[0060] At this time, in the intermediate region filling step, the raw material composition A and the raw material composition B are mixed at different mixing ratios to prepare the (m-2) types of intermediate region HR raw material compositions that give the colors of the "color unit 2" to "color unit m-1". In the pattern 1, the intermediate region HR raw material compositions from the raw material composition for "color unit 2" to the raw material composition for "color unit m-1" are prepared in sequence and the amount required to form each "color unit" is filled into the mold, and in the pattern 2, the intermediate region HR raw material compositions from the raw material composition for "color unit m-1" to the raw material composition for "color unit 2" are prepared in sequence and the raw material composition is changed to fill the amount required to form each "color unit" into the mold.

[0061] The material of the mold used during filling may be metal, ceramics, resin, rubber, etc., depending on the purpose, and it is preferable to use a material that has a higher heat resistance than the polymerization temperature in the curing step described below. Examples of materials for the molding die include SUS, high-speed tool steel, aluminum alloy, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polystyrene (PS), hard rubber, silicone rubber, etc. If necessary, the inner surface of the mold may be subjected to a surface treatment such as an anti-adhesion treatment.

[0062] However, if there is a disturbance at the boundary between adjacent "color units", the desired gradation structure may not be obtained after cutting, and if there is a defect at the boundary, there is a risk of damage starting from that point. For this reason, it is preferable that the cut part has a single-layer structure (a continuous single structure without breaks, substantially uniform except for the color) in which each "color unit" is highly integrated and there is no lamination interface containing disturbances or defects between adjacent "color units". As described above, such a cut part with a single-layer structure can be obtained by a method (hereinafter also referred to as a "continuous filling method") in which a filling device such as a two-liquid mixing dispenser is used in the filling step to scan a nozzle into a mold and continuously extrude and fill the mold while changing the composition slightly "step by step", and such a filling device is also used in the manufacturing method of the present invention.

[0063] A filling device that is preferably used when obtaining a cut portion having a single-layer structure and a continuous filling method using the filling device will be described below.

[0064] 2-3. Suitable filling equipment For the reasons mentioned above, the filling step of the HR raw material composition into the mold is carried out using a storage tank capable of separately holding two types of fluids and a discharge device capable of uniformly mixing the multiple types of fluids held in each storage tank at any ratio and discharging them from a discharge port. As such a discharge device, a discharge device called a multi-liquid mixing dispenser is preferably used. FIG. 2 is a schematic diagram showing the basic structure of a representative multi-liquid mixing dispenser (two-liquid mixing dispenser) 20 that can mix two fluids (liquid compositions), and the liquid compositions stored (held) inside two "storage tank sections" 21a and b are mixed at any ratio in a "mixer section" 24 having a mixing mechanism such as a static mixer or a mixer having a rotation mechanism, and are discharged from a discharge port 26 of a "discharge section" 25 such as a nozzle to fill a mold (molding die) held on a stage section 28. Specifically, "pressurization / depressurization sections" 22a, b are provided on the upstream side of the two "storage tank sections" 21a, b, respectively, and "piping sections" 23a, b leading to a "mixer section" 24 are connected to the downstream sections, and a "control section" (not shown) controls and drives each of the "pressurization / depressurization sections" 22a, b independently to control the extrusion speed and send the liquid compositions to the "mixer section" 24, where the two liquid compositions are uniformly mixed and extruded (discharged) from the discharge port 26 of the "discharge section" 25. At this time, it is of course possible to discharge a single liquid composition as it is from the discharge section 25 (discharge port 26 of the discharge nozzle) without mixing the liquid compositions in the "mixer section" 24. The multi-(2) liquid mixing dispenser shown in FIG. 2 further has an "arm section" 27 for holding the "mixer section" 24, and a "stage section" 28 for holding and placing the mold 30, and is structured so that the relative positional relationship of the discharge port 26 of the "discharge section" 25 with respect to the mold 30 can be freely controlled in the forward / backward / left / right and up / down directions by moving the "arm section" 27 and / or the "stage section" 28 back and forth and up / down by a "control section" not shown (hereinafter, a multi-liquid mixing dispenser having such a structure is also referred to as a "multi-liquid mixing dispenser with a position control mechanism"). The multi-liquid mixing dispenser with a position control mechanism may also have a "heating section" (not shown) for adjusting the temperature as necessary.In a multi-liquid mixing dispenser having such a basic structure, the number of liquid compositions to be mixed can be increased accordingly by increasing the number of sets consisting of the "pressurization / depressurization section," "storage tank section," and piping section connected to the mixer section, so that the combination of types of paste to be mixed in the mixer section and the mixing ratio can be set arbitrarily. Such multi-liquid mixing dispensers with position control mechanisms are widely used for the application of liquid materials such as adhesives in a predetermined pattern during the manufacture of electronic devices (see, for example, Patent Documents 4 and 5), and customized ones are also commercially available.

[0065] By using a multi-liquid mixing dispenser with a position control mechanism, it is possible to simultaneously prepare the paste-like HR raw material composition for "color unit 2" to "color unit m-1" and fill it (into the mold). For example, when using the configuration shown in FIG. 2, if the two "storage tanks" 21a and b are each charged with pre-adjusted raw material compositions A and B, when filling "color unit 1", only raw material composition A is discharged to fill, when filling "color unit m", only raw material composition B is discharged to fill, and when filling "color unit 2" to "color unit m-1", raw material compositions A and B are mixed to form a mixed base of the desired color tone and filled. In addition, when filling a cut part with a different color scheme pattern, for example, where the color of the tip region is A' and the color of the base region is B', raw material compositions A and B may be mixed when filling "color unit 1" and "color unit m", and a paste that gives the color tones of A' and B' may be prepared and filled. Furthermore, a device having three or more "storage tanks" may be used, with a paste-like HR raw material composition imparting a different color tone being charged into each storage tank, and these may be mixed appropriately to prepare a paste for each "color unit" and then filled.

[0066] 2-4. Filling method using a suitable filling device In the case where the filling step is carried out using the two-liquid mixing dispenser with the position control mechanism described above, raw material compositions A and B prepared in advance are charged into two storage tanks, respectively, and only raw material composition A is discharged in the tip region filling step, only raw material composition B is discharged in the base region filling step, and raw material composition A and raw material composition B are appropriately mixed in the intermediate region filling step, thereby simultaneously preparing raw material compositions for each "color unit" that are raw materials for "color unit 2" to "color unit 4 (=m-2)" {(m-2) types of HR raw material compositions for the intermediate region} and filling them, will be described as an example of a continuous filling method.

[0067] When the continuous filling method is performed according to the pattern 1, after the tip region filling step is performed by discharging only the raw material composition A, when the raw material composition A and the raw material composition B are mixed as the intermediate region filling step, the ratio of the raw material composition A in the mixture obtained is gradually reduced to prepare the HR raw material composition for the intermediate region for each "color unit", which is sequentially discharged to perform the intermediate region filling step, and then the base region filling step is performed by discharging only the raw material composition B. When the pattern 2 is adopted, after the base region filling step is performed by discharging only the raw material composition B, when the raw material composition A and the raw material composition B are mixed as the intermediate region filling step, the ratio of the raw material composition B in the mixture obtained is gradually reduced to prepare the HR raw material composition for the intermediate region for each "color unit", which is sequentially discharged to perform the intermediate region filling step, and then the raw material composition A is discharged only to perform the tip region filling step.

[0068] At this time, the filling procedure of the paste-like HR raw material composition is expressed in a coordinate system in which an arbitrary point on the bottom surface of the mold is the origin, the horizontal and vertical directions of the bottom surface are the x-axis and y-axis, respectively, and the height direction is the z-axis. The (m-1) z coordinates corresponding to the height of each boundary between m "color units" to be formed in the mold are expressed as z1 to z2 from the bottom side. m-1 This can be explained as follows. (i) locating the position of the ejection port at the start of filling at the origin; (ii) discharging the HR raw material composition from the discharge port at a predetermined flow rate while moving the position of the discharge port in the x-axis direction and / or the y-axis direction to scan the entire area on the bottom surface once, thereby forming a filling area at the bottom of the mold having a uniform thickness corresponding to the single scan; (iii) after the scanning of (ii) is completed, moving the position of the discharge port in the z-axis direction to a height equal to or higher than the upper surface of the lowermost filling area of ​​the mold; (iv) while discharging the HR raw material composition at a predetermined flow rate in the same manner as in (ii) above, the position of the discharge port is moved in the x-axis direction and / or the y-axis direction to scan the entire area on the upper surface of the bottommost filling area of ​​the mold once, thereby forming a grown filling area with an additional uniform thickness corresponding to the one scan; (v) continuously repeating the operations (iii) and (iv) using the grown filling area as a base; This is done by The ratio of the raw material composition to be discharged is changed so that the thickness of the formed growth filling region is within the range of z1 to z m-1 The operations (ii) to (iv) are performed so that the raw material composition of the next "color unit" is discharged from the discharge port at a timing that coincides or substantially coincides with each height of the first and second "color units."

[0069] By doing so, a blank consisting of a single layer can be efficiently manufactured in a short time. The direction of scanning in the filling region may be selected from the x direction, the y direction, and a combination thereof. For example, a spiral shape starting from the center, a bellows shape starting from one of the four corners, a spiral shape starting from one of the four corners, etc. are examples. It is preferable to change only the (height: z coordinate) without changing the (x, y) coordinates of the end point of the scanning and fill it without interruption as the starting point of the next scanning. In addition, the paste discharge speed during scanning needs to be appropriately adjusted according to the operating speed of the device, but this can be handled by determining in advance in a trial run an amount that is sufficient and does not produce excess. If the amount is too large, the region thickness will be excessive, and if it is insufficient, it will lead to a defective size of the blank, so it is appropriate to determine the amount by trial run so that it is not too much or too little depending on the size of the blank to be manufactured and the required manufacturing speed.

[0070] Using the above-mentioned continuous filling method, color B of "color unit 6 (=m)" is a color tone corresponding to the color tone of the cervical part of the tooth and its adjacent areas, and color A of "color unit 1" is a color tone corresponding to the color tone of the tip area of ​​the tooth. To explain in more detail using the filling process when using pattern 2 to manufacture the cut part 1 shown in Figure 1, from the bottom surface 2 side, "color unit 6 (=m)" 14, "color unit 5 (=m-1)" 15, "color unit 4" 16, "color unit 3" 17, "color unit 2" 18 and "color unit 1" 19 are formed inside the mold, so z1 is the height corresponding to the thickness of "color unit 6 (=m)", z2 is the height corresponding to the total thickness of "color unit 6 (=m)" and "color unit 5 (=m-1)", and similarly z5 is the height corresponding to the total thickness of "color unit 6" to "color unit 2).

[0071] In the above (i) and (ii), for example, when the origin is set at the right front corner of the mold bottom surface 2, the discharge part (discharge port at the tip of the nozzle) discharges only raw material composition B as the paste-like HR raw material composition 40, while moving the discharge part in the direction of the arrow shown in the left diagram of Figures 3 and 4, for example, to scan the entire area on the bottom surface 2 once to form a mold bottom filling region 50 having a uniform thickness corresponding to the one scan, specifically, an (average) thickness corresponding to the height obtained by dividing the total volume (volume) of the paste discharged in the one scan by the bottom area. Then, in (iii) and (iv), as shown in the right diagram of Figure 4, the discharge part is moved upward by the (average) thickness from the point where the one scan ends, and the mold bottom filling region 50 is used as the base (filling region) 51 from that point as the starting point, and the entire area on the upper surface is scanned once to form a grown filling region 52 with an additional uniform thickness corresponding to the one scan. Thereafter, the discharge part is moved upward from the point where the scanning is completed by the added thickness, the entire area of ​​the upper surface of the growing filling area is scanned once, and a new growing filling area with a uniform thickness corresponding to the one scan is formed. This cycle is repeated until the thickness (height) of the new growing filling area matches or is closest to z1, and filling for the base end area 11 is performed. As soon as the filling of the base end area 11 is completed, a predetermined amount of raw material composition A is added to the raw material composition B remaining in the "mixer section" and mixed in the "mixer section" to prepare the raw material for "color unit 2", and then the discharge part is moved upward from the point where the scanning is completed by the added thickness, and this is discharged and operated, and the operation of forming a new growing filling area is repeated until the thickness (height) of the new growing filling area matches or is closest to z2, and filling for "color unit 2" is performed. After that, the mixing ratio of raw material composition B and raw material composition A is changed (the proportion of raw material composition A is increased) to prepare the raw material for "color unit 3", and then the discharge part is moved upward from the point where the scanning ended by the amount of the added thickness, and this is discharged and operated, and the operation of forming a new grown filling region is repeated until the thickness (height) of the new grown filling region coincides with or is closest to z3, thereby filling for "color unit 3". Then, this pattern is repeated until the thickness (height) of the new grown filling region coincides with z3 or is closest to z4. 5(=m-1)This is repeated until the filling of the intermediate region 12 coincides with or is closest to the filling of the color unit 6 (=m), i.e., the filling of the tip region 13, is performed by discharging only the raw material composition A, and the filling process is completed.

[0072] When filling of one blank is completed starting with pattern 2, paste remains in the tip region at the discharge port, so when filling the next blank, it is preferable to start filling from the tip region with pattern 1. In this way, by alternately performing pattern 1 and pattern 2, a large number of blanks can be manufactured continuously.

[0073] 2-5.Curing process A curing step is carried out to polymerize and harden the paste-like HR raw material composition filled in the mold to obtain a mill blank that can be processed. The conditions for hardening the HR raw material composition can be appropriately selected depending on the type of polymerization initiator used. For example, the polymerization temperature when using a thermal polymerization initiator is preferably 60 to 200°C, more preferably 70 to 150°C, and even more preferably 80 to 130°C. If polymerization is carried out at a temperature of 60°C or lower, the polymerization reaction becomes insufficient, the strength of the dental cutting blank becomes weak, and problems such as the occurrence of cracks and deterioration of the physical properties of the processed product arise. On the other hand, if polymerization is carried out at a temperature of 200°C or higher, discoloration of the resin component in the HR progresses, making it difficult to obtain the effect of the present invention, which is color matching with natural teeth. When a photopolymerization initiator is used, it is preferable to perform light irradiation in parallel with filling so that the thickness of the curing target is within 5 mm. If the thickness exceeds 5 mm, light is less likely to penetrate into the HR, so that long-term continuous irradiation is required or physical properties are likely to be poor. For the purpose of further improving the physical properties, a thermal polymerization initiator may be used in combination. In that case, thermal polymerization may be carried out after the above-mentioned steps.

[0074] There is no limitation on the atmosphere during curing, but it is preferable to perform the heat treatment under an inert gas atmosphere such as nitrogen to prevent color change due to oxidation deterioration. There is no limitation on the equipment used for the treatment as long as it can heat the cured body to the desired temperature, but in general, a forced convection oven is preferable to a natural convection oven because it has a higher internal temperature uniformity. There is also no limitation on the method for creating an inert gas atmosphere, but for example, a separate airtight container for storing the cured body may be used, or the oven itself may have an airtight structure to replace the internal atmosphere. Even if the oven is not airtight, a method of continuously flowing atmospheric gas may be used.

[0075] The pressure during curing may be normal pressure, but is preferably 0.1 MPa to 0.9 MPa, and more preferably 0.2 MPa to 0.6 MPa. Such thermal polymerization under pressure can be carried out using a heatable pressure vessel such as a pressure oven or an autoclave.

[0076] Then, the obtained hybrid resin can be subjected to post-processing such as heat treatment, polishing, cutting, attachment of a holder, printing, etc., as necessary. Furthermore, a holding pin for fixing the dental cutting blank to a cutting machine can be joined as necessary. The blank holding pin is not particularly limited as long as it has a shape that allows the blank to be fixed to the cutting machine, and may not be provided depending on the shape of the blank and the requirements of the processing machine. The blank holding pin is made of stainless steel, brass, aluminum, etc. The method of fixing the blank holding pin to the dental cutting resin material does not depend on the above-mentioned adhesion, and may be a method such as fitting or screwing, and the above-mentioned adhesion method is also not particularly limited, and various commercially available adhesives such as isocyanate-based, epoxy-based, urethane-based, silicone-based, and acrylic-based adhesives can be used. EXAMPLES

[0077] In the following, in order to specifically explain the present invention, examples and comparative examples are given, but the present invention is not limited by these. In the examples and comparative examples, "color unit" is expressed as "CU", and "color unit 1" is expressed as "CU1". In addition, the raw materials used in the preparation of the HR raw material composition and their abbreviations are shown below.

[0078] (1) Polymerizable monomer UDMA: 1,6-bis(methacryloyloxycarbonylamino)trimethylhexane 2G: Diethylene glycol dimethacrylate 3G: Triethylene glycol dimethacrylate NPG: Neopentyl dimethacrylate HD: 1,6-Hexanediol dimethacrylate ·UA306H: α,ω-bis(pentaerythritol triacryloxycarbonylamino)hexane ·UA4200: α,ω-bis(acrylethyloxycarbonylamino)decaTHF (2) Inorganic powder and granules F1: Spherical silica zirconia powder with an average particle size of 200 nm, surface-treated with γ-methacryloyloxypropyltrimethoxysilane CF1: 168 parts by mass of powder consisting of agglomerated particles of F1 obtained by spray drying a dispersion of F1, impregnated with 31.2 parts by mass of UDMA as an organic component and 0.8 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) as a polymerization initiator, and then polymerized at 120°C to obtain an organic-inorganic composite powder having an average particle size of 12 μm. F1 content: 84% by mass.

[0079] Example 1 (1) Preparation of raw material composition A for "CU1" (also referred to as paste A) and raw material composition B for "CU5 (=m)" (also referred to as paste B) giving HR of color: B The components of the polymerizable monomer composition containing a polymerization initiator, namely, 50 parts by mass of UDMA, 35 parts by mass of 3G, 15 parts by mass of NPG, and 0.4 parts by mass of benzoyl peroxide, and the components of the powder composition, namely, 200 parts by mass of organic-inorganic composite powder CF1 and 200 parts by mass of inorganic powder F1, were mixed until uniform using a planetary mixer to obtain a base polymerizable curable composition.

[0080] The base polymerizable curable composition was mixed with 100 parts by mass of red pigment (pigment red 166), yellow pigment (pigment yellow 95), blue pigment (pigment blue 60), and white pigment (titanium dioxide) as pigment components to prepare raw material composition A1 (also referred to as paste A1) for "CU1". Separately, the base polymerizable curable composition was mixed with 100 parts by mass of red pigment (pigment red 166), yellow pigment (pigment yellow 95), blue pigment (pigment blue 60), and white pigment (titanium dioxide) as pigment components to prepare raw material composition B (also referred to as paste B1) for "color unit m". These pastes A1 and B1 contain F1 as an inorganic powder and 368 parts by mass in total per 100 parts by mass of polymerizable monomer.

[0081] <Color Tone Evaluation> These pastes A1 and B1 were filled into a polypropylene mold having a hole of φ15 mm, a thickness of 1 mm, length and width of 30 mm, and sandwiched between a polypropylene sheet and a glass plate, and cured body samples were prepared at 95°C for 15 hours. The obtained cured body samples were polished with abrasive paper of no. 2000, and then gloss-polished with a 0.3 μm alumina suspension, and adjusted to 1.0 mm. The L was measured using a spectrophotometer (Tokyo Denshoku Co., Ltd., "TC-1800MKII") under the following measurement conditions: halogen lamp: 12V100W, measurement wavelength range: 380 to 780 nm, reflected light 0°d method (JIS Z8722), measurement area: 5 mmφ, background color: white (a standard white plate was placed over the cured body to block light). * , a * and b *When the measurement was performed, the L * A = 74.6, a * A =-3.4, b * A = 8.6, and for the paste B1 sample (base end region color B1: vita shade corresponds to the color tone of the cervical side of A3), L * B =68.2, a * B =-2.8, b * B = 16.7, which can be calculated using the following formula: Color difference ΔE AB ={(L * A -L * B ) 2 +(a * A -a * B ) 2 +(b * A -b * B ) 2} 0.5 The color difference between the tip region color A1 and the base region color B1 is calculated by: ΔE * AB was 10.3.

[0082] <Evaluation of Viscosity> 0.6 g of each of the obtained pastes A1 and B1 was weighed out, and their viscosities were evaluated by the rotational method using a CS rheometer (Anton Paar MCR302) with a parallel plate of φ20 mm at 25°C and a shear rate of 2 (1 / s). As a result, the viscosity of paste A1 was 134 Pa s, and that of paste B1 was 136 Pa s.

[0083] (2) Manufacturing of HR mill blanks Using a commercially available volumetric two-liquid mixing dispenser (with a position control mechanism) having the same basic configuration as the device shown in Figure 2 and a filling mold with an inner bottom shape of 18.0 mm × 14.5 mm and a height of 14.5 mm, five paste-like HR raw material compositions for CU were filled into the mold by the continuous filling method.

[0084] Specifically, the above-mentioned paste A1 and paste B1, both of which had been vacuum degassed, were charged into one and the other of two "storage tank parts", respectively, and filling was carried out in pattern 1 with "CU1" (tip region) having a thickness of 3.6 mm, "CU2" to "CU4" (middle regions) each having a thickness of 2.4 mm, and "color unit 5" (base region) having a thickness of 3.6 mm. At this time, the mixing ratio A1:B1 of paste A1 and paste B1 for each of the HR raw material compositions for "CU2" to "CU4" was set as follows. In addition, a hardened sample of 1 mm thickness of each of the above-mentioned HR raw material compositions separately prepared was used to perform L * , a * and b * The measurement results were as follows: HR raw material composition A1:B1 L * a * b * For "CU2" 75:25 73.0 -3.3 10.6 For "CU3" 50:50 71.4 -3.1 12.7 For "CU4" 25:75 69.8 -3.0 14.7 The color difference between two adjacent "CU" colors calculated from the above results is: ΔE * xy (where x represents the number of the lower color unit and y represents the number of the upper color unit) is ΔE * 12 = 2.6, ΔE * 23 = 2.6, ΔE * 34 = 2.6, ΔE * 45 =2.6.

[0085] Next, the filled mold was transferred into a heating and pressurizing device, and hardened by heating at 95°C for 15 hours while applying a pressure of 0.4 MPa under a nitrogen atmosphere. After that, the mold was demolded and burrs were removed to produce the number of cut parts required for evaluation. HR-type mill blanks were then produced by attaching CAM retaining pins to these.

[0086] (3) Evaluation of HR mill blanks The obtained HR mill blank was used to fabricate crowns for the canines and molars using a CAD / CAM system, and their appearance was evaluated. The fabricated prostheses, their fabrication method, the details of the evaluation method, and the evaluation results are shown below.

[0087] <The crowns we made and how they were made> A mandibular model with abutment teeth for canines and molars (first premolar, second premolar, first molar) made from core material was scanned with a model scanner, and the attached CAD software (DENTALWING) was used to create STL data for the crowns corresponding to each abutment tooth. Processing paths were then created using CAM software (WORKNC DENTAL: Vero Software). The paths were used to create crowns A to D for the canines and molars with a cutting machine (DWX-52D: DCSHAPE). The heights of the various crowns created are as follows: Mandibular canine crown (Crown A): Height 12mm · Mandibular first premolar crown (Crown B): Height 8mm - Mandibular second premolar crown (Crown C): Height 5.5mm - Mandibular first molar crown (Crown D): Height 4.5mm <Crown evaluation method and evaluation results> In order to confirm whether the crowns fabricated from the HR-series mill blanks could reproduce the gradation of natural teeth regardless of the crown length (height) and furthermore obtain a natural three-dimensional effect after treatment, the following inter-crown appearance comparisons and harmony evaluations were performed.

[0088] [Appearance comparison between crowns] Crowns A to D made using dental resin cement (Estecem II Universal Color: manufactured by Tokuyama Dental) were attached to the abutment teeth of the mandibular model to which the abutment teeth were fixed, and the appearance of adjacent crowns (of different sizes) was compared and evaluated based on the evaluation criteria below. The results were all rated as excellent (◎) between crowns A and B, between crowns B and C, and between crowns C and D.

[0089] Evaluation criteria Excellent (◎): There is almost no difference in appearance and it is in harmony. Good (〇): A difference in appearance can be seen upon careful observation. Fair (△): Differences in appearance are observed upon normal observation, but are at an acceptable level. Poor (x): The difference in appearance is so great that it feels out of place when placed side by side.

[0090] [Harmony evaluation] A set of commercially available artificial teeth consisting of artificial tooth prostheses (porcelain teeth made using a commercially available porcelain system used in general aesthetic restorations. As with dental prostheses in regular private treatments, the tooth structure is reproduced by layering and building up to resemble the appearance of natural teeth) with the color tone of the cervical side equivalent to the shade of the base region color B1: VITA-A3 was prepared, and an abutment tooth corresponding to one of crowns A to D and a crown (one matching this) were attached to the abutment tooth of a mandibular model to which the artificial tooth prostheses other than the abutment tooth were fixed in the same manner as above, and evaluation samples (number of crowns = 4) were prepared. Separately, an upper jaw model to which all the artificial tooth prostheses were fixed was prepared, and the appearance colors were observed with the upper and lower jaw models occluded, and the harmony was evaluated based on the following evaluation criteria. Crown A was excellent, crown B was excellent, crown C was excellent, and crown D was excellent. Excellent (◎): The crown restoration blends in with the surrounding area, and the color transition of the restoration is the same as that of the artificial tooth. Good (〇): The crown restoration can be recognized upon careful observation, and the color transition of the restoration is similar to that of an artificial tooth. Fair (△): The crown restoration can be recognized by normal observation, but is at an acceptable level. Poor (×): The repaired area is visible at a glance and gives an unpleasant feeling.

[0091] <Bending strength evaluation> The dental hardenable composition thus obtained was devoid of air bubbles, and filled into a mold of 12×15×5 (mm), and then thermally polymerized at 95° C. for 15 hours to obtain a dental hardened product. The hardened product thus obtained was then cut out with a low-speed diamond cutter (manufactured by Buehler Co., Ltd.), and then trimmed into a prism shape of 1.2 mm×4.0 mm×15 mm using waterproof abrasive paper of size 2000 to obtain a test piece. The test piece was mounted on an autograph (manufactured by Shimadzu Corporation), and a three-point bending test was carried out under the conditions of a support distance of 12 mm and a crosshead speed of 1 mm / min. Bending strength σ is calculated by the formula: σ = 3PS / 2WB 2 In the above formula, P means the bending load (N) at the maximum point, S means the distance between the supports (12 mm), W means the width of the sample (about 4.0 mm), and B means the thickness of the sample (about 1.2 mm). Five test pieces were prepared, and the average value was taken as the bending strength of the dental hardened material.

[0092] <Surface hardness evaluation> The dental resin composition obtained by the above method was cut out with a low-speed diamond cutter (manufactured by Buehler), polished with 2000 grit waterproof abrasive paper and 0.3 μm alumina particles, and shaped into a prism shape of 12 mm × 14 mm × 1.0 mm to obtain a test piece. Then, using a microhardness tester (MHT-1, manufactured by Matsuzawa Seiki), the diagonal length (d) of the indentation made under a load condition of 200 gf for 30 seconds was measured, and the surface hardness of the test piece was calculated. The surface hardness Hv was calculated according to the formula: Hv = 1854.37 × 100 g / d 2 The calculation was made as follows.

[0093] Examples 2 to 8 (1) Preparation of Paste A and Paste B The following pastes A2 to A8, which will become paste A, and the following pastes B2 to B8, which will become paste B, were prepared in the same manner as in Example 1 using the same powder composition and pigment components as in Example 1, except that the type and amount of the polymerizable monomer to be blended were changed as shown in Table 1. Paste A2-8 (tip area color: vita shade corresponds to the incisal side color of A1) A2L * = 74.8, a * =-3.6, b * =8.1 A3 L * = 74.0, a * =-3.3, b * =8.9 A4 L * = 75.0, a * =―3.0, b * =8.5 A5 L * = 74.1, a * =-3.7, b * =8.6 A6 L * = 75.1, a * =-2.9, b * =7.9 A7 L * = 73.5, a * =-3.2, b * =8.4 A8 L * = 74.0, a * =―3.0, b * =8.2 Paste B2-8 (proximal region color: vita shade corresponds to the cervical side color of A3) B2 L * =68.8, a * =-2.7, b * =15.9 B3 L * =69.0, a * =-2.5, b * =16.9 B4 L * =69.3, a * =-2.7, b * =16.3 B5 L * =69.2, a * =-2.8, b * =16.6 B6 L * = 70.1, a * =―3.0, b * =16.7 B7 L* =69.9, a * =-2.6, b * =16.8 B8 L * =69.7, a * =-2.4, b * =16.0.

[0094] (2) Manufacturing of HR mill blanks A combination of one selected from each of pastes A and B, including pastes A1 and B1, was used to prepare a cut part having a CU number m=5 in accordance with Example 1, and an HR-type mill blank was manufactured in the same manner as in Example 1. The paste combinations in each Example, ΔE AB The mixing ratio of paste A and paste B in the preparation of each HR raw material composition for "CU2" to "CU4" was A:B, and a 1 mm sample of the hardened HR raw material composition prepared in the same manner was used to measure L * , a * and b * etc. are shown below.

[0095] Example 2: Using Paste A2 and Paste B2 (ΔE AB =9.9). HR raw material composition A2:B1 L * a * b * For "CU2" 75:25 73.3 -3.4 10.1 For "CU3" 50:50 71.8 -3.2 12.0 For "CU4" 25:75 70.3 -2.9 14.0 ΔE 12 = 2.5, ΔE 23 = 2.5, ΔE 34 = 2.5, ΔE 45 =2.5.

[0096] Example 3: Using Paste A3 and Paste B3 (ΔE AB =9.5). HR raw material composition A1:B2 L * a * b * For "CU2" 75:25 72.8 -3.1 10.9 For "CU3" 50:50 71.5 -2.9 12.9 For "CU4" 25:75 70.3 -2.7 14.9 ΔE 12 = 2.4, ΔE 23 = 2.4, ΔE 34 = 2.4, ΔE 45 =2.4.

[0097] Example 4: Paste A4 and Paste B4 (ΔE AB =9.7). HR raw material composition A1:B3 L * a * b * For "CU2" 75:25 73.6 -2.9 10.5 For "CU3" 50:50 72.2 -2.9 12.4 For "CU4" 25:75 70.7 -2.8 14.4 ΔE 12 = 2.4, ΔE 23 = 2.4, ΔE 34 = 2.4, ΔE 45 =2.4.

[0098] Example 5: Paste A5 and Paste B5 (ΔE AB =9.4). HR raw material composition A1:B3 L * a * b * For "CU2" 75:25 72.9 -3.5 10.6 For "CU3" 50:50 71.7 -3.3 12.6 For "CU4" 25:75 70.4 -3.0 14.6 ΔE 12 = 2.4, ΔE 23 = 2.4, ΔE 34 = 2.4, ΔE 45 =2.4.

[0099] Example 6: Paste A6 and Paste B6 (ΔE AB=10.1). HR raw material composition A1:B3 L * a * b * For "CU2" 75:25 73.9 -2.9 10.1 For "CU3" 50:50 72.6 -3.0 12.3 For "CU4" 25:75 71.4 -3.0 14.5 ΔE 12 = 2.5, ΔE 23 = 2.5, ΔE 34 = 2.5, ΔE 45 =2.5.

[0100] Example 7: Paste A6 and Paste B6 (ΔE AB =9.2). HR raw material composition A1:B3 L * a * b * For "CU2" 75:25 72.6 -3.1 10.5 For "CU3" 50:50 71.7 -2.9 12.6 For "CU4" 25:75 70.8 -2.8 14.7 ΔE 12 = 2.3, ΔE 23 = 2.3, ΔE 34 = 2.3, ΔE 45 =2.3.

[0101] Example 8: Paste A6 and Paste B6 (ΔE AB =8.9). HR raw material composition A1:B3 L * a * b * For "CU2" 75:25 72.9 -2.9 10.2 For "CU3" 50:50 71.7 -2.7 12.1 For "CU4" 25:75 70.8 -2.6 14.1 ΔE 12 = 2.2, ΔE 23 = 2.3, ΔE 34 = 2.2, ΔE45 =2.2.

[0102] [Table 1]

[0103] (3) Evaluation of HR mill blanks The obtained HR-based mill blank was used to prepare a crown specimen in the same manner as in Example 1, and the bending test specimen and surface hardness were evaluated. The results are shown in Table 2. The harmony evaluation in each Example was performed using a full set of artificial teeth having the same shade of the cervical side as the shade of the paste B used.

[0104] [Table 2]

[0105] Comparative Example 1 Pastes were prepared in the same manner as in Example 1, except that the types and amounts of polymerizable monomers and pigments to be blended were changed as shown in Table 3, and various test specimens were fabricated and evaluated. The results are shown in Tables 3 and 4. The composition had a high paste viscosity, and mixing and discharging were not possible, so a crown could not be produced.

[0106] Comparative Example 2 The powder composition to be blended was 50 parts by mass of organic-inorganic composite powder CF1 and 50 parts by mass of inorganic powder F1 (containing 92 parts by mass of F1 as inorganic powder in total per 100 parts by mass of polymerizable monomer). Except for changing the types and amounts of polymerizable monomer and pigment blended as shown in Table 3, pastes were prepared in the same manner as in Example 1, and various test specimens were produced and evaluated. The evaluation results are shown in Tables 3 and 4. Because this composition had a low paste viscosity, the color unit interfaces were curved and layered during mixing and discharging, resulting in an unnatural appearance.

[0107] [Table 3]

[0108] [Table 4] [Explanation of symbols]

[0109] 1... Part to be cut 2. Bottom 3...Top surface 10. Gradient structure of the present invention 11...Proximal region (proximal region color A) 12...middle area (middle area color C: C2~C5) 13...Tip area (Tip area color B) 14...Color unit 6 (color unit m) 15···Color unit 5 (Color unit m-1) 16...Color Unit 4 17. Color Unit 3 18...Color Unit 2 19...Color Unit 1 20...Two-liquid mixing dispenser (multi-liquid mixing dispenser with position control mechanism) 21a,b... Storage tank section 22a,b Pressurization / decompression section 23a,b... Piping section 24 Mixer section 25...Discharge part 26...Discharge port 27 Arm section 28. Stage section 30. Mold 40 Paste-like HR raw material composition 50···Mold bottom filling area 51...Base (filling area) 52...growth filling area

Claims

1. A method for manufacturing a mill blank for dental cutting, comprising: a hybrid resin having a columnar shape with a bottom surface and a top surface having substantially the same shape; and a cutting portion having a gradation structure in which the appearance color changes stepwise in the height direction when the direction from the bottom surface of the columnar body to the top surface, which is the tip, is defined as the height direction, the method comprising: The gradation structure is such that the regions exhibiting the same appearance color constitute "color units" of a predetermined thickness obtained by dividing the columnar body in the height direction by a plane horizontal to the bottom surface, and 3 to 9 "color units" having different appearance colors are continuously arranged in the height direction, The 3 to 9 "color units" are represented as "color unit n" by assigning unit numbers n (where m is a natural number in the range of 3 to 9 representing the number of units) from 1 to m in order from the distal end to the proximal end, and the color of the "color unit 1" located at the distal end is designated as "tip region color: A" and the color of the "color unit m" located at the proximal end is designated as "proximal region color: B." Color difference between the distal end region color: A and the proximal end region color: B: ΔE AB is 5 to 20, In the "color unit 2" to the "color unit m-1", the colors of these units are all intermediate colors C between the distal region color A and the proximal region color B, and change stepwise from an intermediate color close to the distal region color A to an intermediate color close to the proximal region color B from the "color unit 2" to the "color unit m-1", and the color difference between the colors of adjacent units is ΔE C is 1 to 7, The manufacturing method includes: The method includes a raw material preparation step of preparing a paste-like HR raw material composition containing 100 parts by mass of a polymerizable monomer, 300 to 900 parts by mass of inorganic powder and granules constituted by inorganic particles, a polymerization initiator, and a colorant, the paste having a viscosity of 20 to 150 (Pa·s) as measured with a rotational viscometer at 25° C.; a filling step of filling the HR raw material composition into a mold corresponding to the shape of the cut portion; and a hardening step of hardening the HR raw material composition filled in the mold, In the raw material preparation step, as HR raw material compositions, a raw material composition A for "color unit 1" that imparts an HR of the tip region color: A, a raw material composition B for "color unit m" that imparts an HR of the base region color: B, and (m-2) types of HR raw material compositions for intermediate regions that have compositions equivalent to a mixture of the raw material composition A and the raw material composition B and that impart the appearance colors of the "color unit 2" to "color unit m-1" are prepared; The filling step includes: a tip region filling step of filling a necessary amount of the raw material composition A into the mold to form the "color unit 1"; a base end region filling step of filling a necessary amount of the raw material composition B into the mold to form the “color unit m”; and a filling step for filling a necessary amount of the HR raw material composition for the intermediate region into the mold to form the "color unit 2" to "color unit m-1", The filling step is (1) Pattern 1, in which the distal region filling step, the intermediate region filling step, and the proximal region filling step are performed in this order, or (2) Pattern 2 in which the base region filling step, the intermediate region filling step, and the tip region filling step are performed in this order. This is done in one of the following patterns: In the filling step, the filling is performed using storage tanks capable of separately holding two types of fluids and a discharge device capable of uniformly mixing the two types of fluids held in each storage tank at an arbitrary ratio and discharging the mixture from a discharge port; In the pattern 1, the discharge device is used to discharge only the raw material composition A to perform the tip region filling step, and then, when mixing the raw material composition A and the raw material composition B in the intermediate region filling step, the ratio of the raw material composition A in the resulting mixture is gradually reduced to prepare an intermediate region HR raw material composition for each "color unit", which is discharged sequentially to perform the intermediate region filling step, and then, only the raw material composition B is discharged to perform the base region filling step, In the pattern 2, the base end region filling step is performed by discharging only the raw material composition B using the discharge device, and then, in the intermediate region filling step, when mixing the raw material composition A and the raw material composition B, the ratio of the raw material composition B in the resulting mixture is gradually reduced to prepare an intermediate region HR raw material composition for each "color unit", which is sequentially discharged to perform the intermediate region filling step, and then, the tip region filling step is performed by discharging only the raw material composition A. A method for producing a mill blank for dental cutting, comprising the steps of:

2. In the intermediate region filling step, the raw material composition A and the raw material composition B are mixed at different mixing ratios to prepare the (m-2) types of intermediate region HR raw material compositions that give the colors of the "color unit 2" to "color unit m-1": In the pattern 1, intermediate region HR raw material compositions from a raw material composition for "color unit 2" to a raw material composition for "color unit m-1" are prepared in sequence, and the amount required to form each "color unit" is filled into the mold. In the pattern 2, intermediate region HR raw material compositions from a raw material composition for "color unit m-1" to a raw material composition for "color unit 2" are prepared in sequence, and the raw material composition is changed to fill the amount required to form each "color unit" into the mold. The method for producing the dental cutting mill blank according to claim 1 .

3. The position in the mold is expressed in a coordinate system in which an arbitrary point on the bottom surface of the mold is the origin, the horizontal and vertical directions of the bottom surface are the x-axis and y-axis, respectively, and the height direction is the z-axis. (m-1) z-coordinates corresponding to the heights of each boundary between m "color units" to be formed in the mold are expressed as z-coordinates from the bottom surface side. 1 ~z m-1 When In the filling step, the raw material compositions for the various "color units" are filled into the mold using the discharge device that can freely control the position of the discharge port in the front-back direction, the left-right direction, and the height direction. (i) locating the position of the ejection port at the start of filling at the origin; (ii) discharging the HR raw material composition from the discharge port at a predetermined flow rate while moving the position of the discharge port in the x-axis direction and / or the y-axis direction to scan the entire area on the bottom surface once, thereby forming a mold bottom filling area having a uniform thickness corresponding to the single scan; (iii) after the scanning of (ii) is completed, moving the position of the discharge port in the z-axis direction to a height equal to or higher than the upper surface of the lowermost filling area of ​​the mold; (iv) while discharging the HR raw material composition at a predetermined flow rate in the same manner as in (ii) above, the position of the discharge port is moved in the x-axis direction and / or the y-axis direction, and the entire area on the upper surface of the bottommost filling area of ​​the mold is scanned once to form a grown filling area with an additional uniform thickness corresponding to the single scan; (v) continuously repeating the operations (iii) and (iv) using the grown filling area as a base; This is done by The ratio of the raw material composition to be discharged is changed so that the thickness of the formed growth filling region becomes z 1 ~z m-1 The operations (ii) to (iv) are performed so that the raw material composition of the next "color unit" is discharged from the discharge port at a timing that coincides or substantially coincides with each height of the The method for producing a mill blank for dental cutting according to claim 2 .

4. A dental hardenable composition for an HR raw material composition in the method for producing a mill blank for dental cutting according to claim 1, Polymerizable monomer: 100 parts by mass, inorganic powder / granules constituted by inorganic particles: 300 to 900 parts by mass, a polymerization initiator and a colorant are included, CH 2 ═C(R)—COO— or CH 2 In a polyfunctional radically polymerizable monomer compound having 2 to 6 radically polymerizable groups represented by =C(R)-CONH- (wherein R in these groups is a hydrogen atom or a methyl group) in the molecule, when the number of atoms constituting the main chain of the divalent organic group having the largest number of atoms constituting the main chain among the divalent organic groups interposed between any two radically polymerizable groups selected from the 2 to 6 radically polymerizable groups contained in the molecule of the polyfunctional radically polymerizable monomer compound is α, the polyfunctional radically polymerizable monomer compound having α of 1 to 9 is a short-chain monomer, and the polyfunctional radically polymerizable monomer compound having α of 10 to 60 is a long-chain monomer, the polymerizable monomer comprises the short-chain monomer and the long-chain monomer, and the content of the short-chain monomer in the polymerizable monomer is 45 to 90 mass %; A dental hardenable composition comprising:

5. the short chain length monomer comprises at least one compound selected from the group consisting of alkyl dimethacrylates and polyalkylene glycol dimethacrylates; 5. The dental hardenable composition according to claim 4, wherein the long-chain monomer comprises at least one compound selected from urethane (meth)acrylates.

6. 5. The dental curable composition according to claim 4, wherein the inorganic powder and granules are constituted by spherical or nearly spherical inorganic particles, and contain inorganic spherical powder and granules having a particle diameter D50p of 50 to 500 nm, which is a cumulative 50% particle diameter from the small diameter side in a number-based particle size distribution measured by a laser diffraction method, and the amount of the inorganic nearly spherical powder and granules in the inorganic powder and granules is 40 mass% or more.

7. 5. The dental hardenable composition according to claim 4, which has a viscosity of 20 to 150 (Pa·s) at 25° C. as measured with a rotational viscometer.

Citation Information

Patent Citations

  • JP1987085909A

  • Transfer-type thermal recording method

    JP1988049480A

  • dental mill blank

    JP2016535610A

  • Method and apparatus for manufacturing dental processing blank of multilayer structure

    JP2020151339A

  • Dental shaped bodies with continuous shade gradient

    US20190247168A1